The Influence of National Characteristic Squares on Urban Space and Society - Jieqiong, Jiao; Malek, Nurhayati Abdul (Journal of Ecohumanism, 2024)
As urbanisation accelerates, urban landscape design assumes increasing significance. Within the multicultural context of China, integrating national cultural elements into urban landscape design is a noteworthy endeavour for preserving and enriching national heritage. This study aims to comprehensively investigate and analyse the distinct features of Chinese Mongolian ethnic elements and their application within square landscape design. It delves into various influential factors, including government policies, designer education, media influence, and international collaborations, concerning implementing Mongolian ethnic elements in square landscapes. We aspire to offer theoretical underpinnings and practical guidance for further advancing Chinese square landscape design. Our efforts aim to enrich urban culture, enhance urban quality, and foster a greater sense of national cultural identity.